Comparison of long-read sequencing and MLPA combined with long-PCR sequencing of CYP21A2 mutations in patients with 21-OHD - Lan, Tian; Wang, Jin; Chen, Kaibi; Zhang, Jianru; Chen, Xiaohong; Yao, Hui (Frontiers in Genetics, 2024)
Background 21-Hydroxylase deficiency (21-OHD) is caused by mutations in the CYP21A2 gene. Due to the complex structure and the high genetic heterogeneity of the CYP21A2 gene, genetic testing for 21-OHD is currently facing challenges. Moreover, there are no comparative studies on detecting CYP21A2 mutations by both second-generation sequencing and long-read sequencing (LRS, also known as third-generation sequencing). Objective To detect CYP21A2 variations in 21-OHD patients using targeted capture with LRS method based on the PacBio (Pacific Biosciences) Sequel II platform. Methods A total of 67 patients with 21-OHD were admitted in Wuhan Children’s Hospital. The full sequence of CYP21A2 gene was analyzed by targeted capture combined with LRS based on the PacBio Sequel II platform. The results were compared with those of long-polymerase chain reaction (Long-PCR) combined with multiplex ligation probe amplification (MLPA) detection. Based on the in vitro study of 21-hydroxylase activity of common mutations, the patient genotypes were divided into groups of Null, A, B, and C, from severe to mild. The correlation between different genotype groups and clinical typing was observed. Results The study analyzed a total of 67 patients. Among them, 44 (65.67%) were males and 23 (34.33%) were females, with a male-to-female ratio of approximately 1.9:1. A total of 27 pathogenic variants were identified in the 67 patients, of which micro-conversion accounted for 61.9%, new variants of CYP21A2 accounted for 8.2%; deletion accounted for 22.4% (CYP21A2 single deletion and chimeric TNXA/TNXB accounted for 12.7%, chimeric CYP21A1P/CYP21A2 accounted for 9.7%); and duplication accounted for 3.0% (CYP21A2 Gene Duplication). I2G was the most common variant (26.9%). Targeted capture LRS and MLPA combined with Long-PCR detection of CYP21A2 mutations showed 30 detection results with differences. The overall genotype-phenotype correlation was 82.1%. The positive predictive rate of the Null group for salt wasting (SW) type was 84.6%, the A group for SW type was 88.9%, the group B for simple virilization (SV) type was 82.4%, and the group C for SV type was 62.5%. The correlation coefficient rs between the severity of the phenotype and the genotype group was 0.682 (P < 0.05). Conclusion Targeted capture combined with LRS is an integrated approach for detecting CYP21A2 mutations, allowing precise determination of connected sites for multiple deletions/insertions and cis/trans configurations without analyzing parental genomic samples. The overall genotype-phenotype correlation for 21-OHD is generally strong, with higher associations observed between genotype and phenotype for group Null, A, and B mutations, and larger genotype-phenotype variation in group C mutations. Targeted capture with LRS sequencing offers a new method for genetic diagnosis in 21-OHD patients.